J 5 — A Data Processing System for Medical Information - Hall, P.; Mellner, Ch.; Danielsson, T. (Methods of Information in Medicine, 1967)
A system for medical information has been developed. The system is a general and flexible one which without reprogramming or new programs can accept any alphabetic and/or numeric information. Coded concepts and natural language can be read, stored, decoded and written out. Medical records or parts of records (diagnosis, operations, therapy, laboratory tests, symptoms etc.) can be retrieved and selected. The system can process simple statistics but even make linear pattern recognition analysis.The system described has been used for in-patients, outpatients and individuals in health examinations.The use of computers in hospitals, health examinations or health care systems is a problem of storing information in a general and flexible form. This problem has been solved, and now it is possible to add new routines like booking and follow-up-systems. •